Poor Quality of Treated Water in Kathmandu: Comparison with Nepal Drinking Water Quality Standards (Tribhuvan University Journal of Microbiology, 2018)
Objectives: In order to evaluate the quality assurance of drinking water in Kathmandu valley, this study analyzed selected physiochemical and microbial parameters of treated water samples and compared with Nepal Drinking Water Quality Standards (NDWQS).Methods: Treated water samples were collected from all over the Kathmandu valley and analyzed in terms of physicochemical and microbiological parameters over the period of one year from July 2017 to July 2018. The physio-chemical parameters of water samples were performed according to standard methods for the examination of water and wastewater. The total coliforms were enumerated by standard membrane filtration technique.Results: We report that microbiological aspect of treated water was the major problem as 66% of the water samples crossed the guideline value for total coliform count. Above 92% of jar water samples, 77% of tanker water samples and 69% of filtered water samples had the total coliform count exceeding the NDWQS. Moreover, 20% of bottled water was contaminated by coliform bacteria. Iron and ammonia content were found to be higher than the guideline values in 16% and 21% of the total treated water samples respectively. Analyzing the types of treated water samples showed that 35% and 15% of tanker water samples had higher ammonia and iron content respectively, and the same parameters were higher in 23% and 19% in the filtered water samples respectively than the standard criteria recommended by NDWQS.Conclusion: The treated water samples exceed the standard values set by NDWQS and hence had poor quality. The presence of faecal pollution indicating coliform bacteria was the key problem for treated drinking water of Kathmandu valley. Therefore, monitoring and proper treatment of water should be conducted to prevent dissemination of waterborne diseases.